OPTIMALISASI PEMBELAJARAN ANALISIS PEMODELAN BANGKITAN PERJALANAN MENGGUNAKAN APLIKASI SPSS PADA MATA KULIAH PERENCANAAN DAN PEMODELAN TRANSPORTASI PRODI S1 SIPIL FAKULUTAS TEKNIK UNIVERSITAS RIAU - Rizqy Ridho Praksa; Edi Yusuf Adiman; Benny Hamdi Rhoma Putra (Yayasan Wayan Marwan Pulungan, 2023)
The importance of mastering skills in statistical analysis in the field of transportation planning and modeling has not been supported by learning to use the SPSS application so that the teaching and learning process is not optimal for students of the Civil Engineering Study Program at Riau University. The purpose of this optimization is to provide knowledge to undergraduate students of Civil Engineering, Riau University in order to gain specific skills, namely modeling trip generation using the SPSS application. Optimization method by introducing the SPSS application and making teaching modules in modeling trip generation, Pre Test to find out student knowledge related to the SPSS application, ending with Post Test activities as evaluation material. The results of the Pre Test were 50-60% of students did not know the application, while the Post Test results were 90% of students knew the use of the SPSS application in modeling trip generation well. It is hoped that this optimization will increase knowledge and skills which can later become a plus point in the world of work.